Ebu’l-Hayr Abdulmecid B. Muharrem Es-Sivasi (971-1049 / 1563-1639)’nin “Fatiha Tefsiri” nin tahkiki - Kılıç, Mustafa (My University, 2005)
TEZ ÖZETİ Abdulmecîd Sîvâsî (ö.1049/ 1639) Halvetiyye tarikatının Şemsiyye koluna mensup bir şeyhtir. Sultan III. Mehmet'in daveti üzerine İstanbul'a yerleşmiş ve vefatına kadar talim faaliyetini orada sürdürmüştür. O, bu talim faaliyetlerinin yanı sıra yaklaşık 20 eser kaleme almıştır. Bunlardan bir tanesi de, tez konusu olarak çalıştığımız, Tefsir-i Sureti'l - Fatiha adlı eseridir. Biz bu çalışmamızda söz konusu eserin transkripsiyon ve tahkikini amaçladık. Çalışmamızı, eserin elyazması olarak ulaşabildiğimiz dört nüshası etrafında gerçekleştirdik. Çalışma içerisinde, öncelikle eldeki dört nüshayı karşılaştırarak, bunlar arasındaki farklılıkları tesbit etmeye çalıştık.. Eserde geçen ayetlerin sure ve ayet numaralarını tesbit edip, hadislerin tahricini yaptık. Ayrıca eserde zikredilen müellifler hakkında verdik. Sivasi'nin dokuz bölüm halinde ele aldığı eseri, anlaşılmasına kolaylık sağlama düşüncesiyle alt başlıklara ayırdık ve tezin sonuna bir de sözlük kısmı ekledik. Mustafa KILIÇ Supervisor: Yar. Doç. Dr. Fatih ÇOLLAK Abdulmecid Sivasi ( d.: 1049/ 1639) was a master of the Halvetiyye Order. He was bound to the Şemsiyye branch of Halvetiyye. He had settled down Istanbul on invitation of Sultan Mehmed the third and gone on activity of instruction there till the death. At the same tame he approximately wrote 20 books. One of them is The İnterpretation of Sura al-Fatiha that we studied as the subject of the thesis.The aim of our study is the transcription and the investigation of this book. We made up the study around four manuscripts of the book that we could find. During the study we primarily tried to compare these four manuscripts and to discover the distinction between them. We added the names of Sura and the number of Kuran's verses that took part in the manuscripts. At the same tame, we ascertained the basic root of the hadiths written in the manuscripts. We also gave a general information about the writers whom mentioned. The book that Sivasi treated as nine chapters, we divided it new/ lower titles, aiming at making it more understandable. We also added the glossary at the end of the thesis.
Keywords: Abdulmecîd Sîvâsî (ö.1049/ 1639); Fatiha Tefsiri; Tefsir